A Novel Rabies Vaccine Based on a Recombinant Bovine Herpes Virus Type 1 Expressing Rabies Virus Glycoprotein - Zhao, Caiquan; Gao, Jie; Wang, Yongzhi; Ji, Lina; Qin, Hui; Hu, Wei; Yang, Yang (Frontiers in Microbiology, 2022)
Rabies is a highly prevalent zoonotic disease and a public health threat worldwide. Currently licensed rabies vaccines are effective but less are known they would provide protection for cattle. This present study describes the construction of a novel recombinant bovine herpesvi-rus type I (BHV-1) expressing rabies virus glycoprotein (RABV G) instead of its own gE glycoprotein (gE) by CRISPR-Cas9 and homolo-gous recombination technology (BHV-1-ΔgE-G). Insertion of RABV G gene is stable after 20 rounds of in vitro passaging and the recom-binant virus replicates to high titers in MDBK cells. The RABV G expresses in the recombinant virus infected cells and on the virion sur-face of BHV-1-ΔgE-G. One single immunization with BHV-1-ΔgE-G activated dendritic cells (DCs) and B cells, furthermore induced a protective immune response in mice against severe lethal challenge infection. Protective level of RABV specific virus neutralizing antibody (VNA) were detected in intramuscular immunized mice and cattle without any clinical symptoms. This research demonstrated the BHV-1 vector based RABV vaccine is a potential candidate for cattle.